Review: Progress and potential of DNA barcoding for species identification of fish species - AYESHA IMTIAZ; SITI AZIZAH MOHD NOR; DARLINA MD. NAIM (Society for Indonesian Biodiversity, 2017)
Imtiaz A, Mohd Nor SA, Md. Naim D. 2017. Review: Progress and potential of DNA barcoding for species identification of fish species. Biodiversitas 18: 1394-1405. DNA barcoding is a molecular technique to identify species by utilizing 600-800 base pairs genetic primer segments of mitochondrial gene cytochrome oxidase I. DNA barcoding has high potential to identify species into taxa, resolves ambiguousness in species identification, helps in accurate species identification, categorize species for conservation and also communize the information in the form of database system. The main challenge to this technique is regarding the use of barcoding information on ‘biological species concept’. The extreme diversity of fish and their economic importance has made this group a major target of DNA barcoding. DNA barcoding can assign the status of known to unknown sample but it also has the ability to detect previously un-sampled species as distinct. In this review, we present an overview of DNA barcoding and introduce current advances and limitation of this promising technique.